Mathematics Teachers’ Perceptions of Difficulties Encountered by Students in Geometric Constructions in Egbeda Local Government Area, Oyo State, Nigeria - Sam-Kayode, Christianah Olajumoke (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study assessed Mathematics teachers’ perceptions of the difficulties encountered by students in geometric constructions in Egbeda Local Government Area, Oyo State, Nigeria. A qualitative research design was adopted for the study using a 30-item self-structured questionnaire administered on Thirty-five (35) Mathematics teachers from sixteen (16) secondary schools, selected through simple random sampling techniques. The schools were sampled based on the followings: Presentations of candidates for the West African School Certificate Examinations for at least twenty years (2004-2023); availability of at least two qualified Mathematics teachers who teach at senior secondary school; availability of Mathematics laboratories, moderately populated classrooms; and sufficient periods for Mathematics lessons on the timetable. The following conclusions were arrived at which include; insufficient number of teachers to teach Mathematics in some of the schools, lack of skillful teachers who are versed in the concept of geometric construction, lack of construction instruments (Mathematical set) by some of the students, insufficient time/periods allocated to Mathematics lessons, laxity by students in practicing geometric constructions at home and overcrowded classrooms. This study recommended that: More Mathematics teachers should be employed to teach Mathematics at the secondary schools, Mathematics Teachers should update their knowledge in the rudiments of the concept of geometric constructions, students should be encouraged to get construction instruments(Mathematical set) to aid their learning of geometric constructions, sufficient time/periods should be allocated to Mathematics lessons, students should be encouraged to practice geometric constructions at home, and school administrators should work on reducing overcrowded classrooms to manageable ones.